Riboflavin Is Ineffective For Maternally Inherited Mitochondrial Disease - Finsterer, MD, PhD, Josef; Mahjoub, PhD, Sinda Zarrouk (Journal of Medical Biomedical and Applied Sciences, 2018)
With interest we read the article by Darin et al. about 13members of a family carrying the m.3250T>C mutation inthe tRNA(Leu) gene on the mitochondrial DNA1. Two ofthese patients were systematically treated with riboflavin butwithout a beneficial effect1. We have the followingcomments and concerns.